3x+2x-2=4x+x+2

Simple and best practice solution for 3x+2x-2=4x+x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+2x-2=4x+x+2 equation:


Simplifying
3x + 2x + -2 = 4x + x + 2

Reorder the terms:
-2 + 3x + 2x = 4x + x + 2

Combine like terms: 3x + 2x = 5x
-2 + 5x = 4x + x + 2

Reorder the terms:
-2 + 5x = 2 + 4x + x

Combine like terms: 4x + x = 5x
-2 + 5x = 2 + 5x

Add '-5x' to each side of the equation.
-2 + 5x + -5x = 2 + 5x + -5x

Combine like terms: 5x + -5x = 0
-2 + 0 = 2 + 5x + -5x
-2 = 2 + 5x + -5x

Combine like terms: 5x + -5x = 0
-2 = 2 + 0
-2 = 2

Solving
-2 = 2

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -0.2-q=9q | | X*.05833333333=(X-113) | | N^7/10 | | 2g+3G=10 | | 4(-y+2)=-1 | | X/3=70 | | N^10/7 | | 2m+-3m-8=26 | | Px+Q=X+1 | | 2x+4(2x+8)=10x+32 | | 1+8x^2+x^4= | | 90=(4x+12)+(6x+8) | | 4In(2x+3)=11 | | .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) |

Equations solver categories